1989
DOI: 10.1096/fasebj.3.12.2477295
|View full text |Cite
|
Sign up to set email alerts
|

Lack of sensitivity to ouabain in natural killer activity

Abstract: Natural killer (NK) activity against K562 target cells is not an ouabain‐sensitive process. Inhibition of 40% of cytotoxicity was achieved only with an ouabain concentration much higher than that required to inhibit cell activation in other systems such as leukocyte chemotaxis and B lymphocyte plaque formation. Pre‐treatment of effector cells with biological agents such as phorbol‐ester 12‐O‐tetradecanoylphorbol‐13‐acetate or interferon increased the cytotoxicity. This activation was not counteracted by ouabai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Ouabain, in vitro , inhibits mitogen-induced thymocyte and lymphocyte proliferation [10, 11], inhibits the generation of lymphokine-activated killer (LAK) activity induced by IL-2 [12], increases intracellular calcium levels [13], increases CD69 expression [14] and acts both in vitro [15] and in vivo [16] synergistically with corticoids. In vitro , ouabain increases glucocorticoid-induced plasma membrane depolarization in lymphoid cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Ouabain, in vitro , inhibits mitogen-induced thymocyte and lymphocyte proliferation [10, 11], inhibits the generation of lymphokine-activated killer (LAK) activity induced by IL-2 [12], increases intracellular calcium levels [13], increases CD69 expression [14] and acts both in vitro [15] and in vivo [16] synergistically with corticoids. In vitro , ouabain increases glucocorticoid-induced plasma membrane depolarization in lymphoid cells [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of workers, including ourselves, has described the inhibitory effects of ouabain on lymphocyte proliferation induced by various stimuli such as mitogens (Szamel et al 1981, Moraes et al 1989, Olej et al 1998, phorbol ester (Olej et al 1994, Brodie et al 1995, CD3 (Szamel et al 1995), Interleukin-2 (Redondo et al 1986) and calcium ionophore (Jensen et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of workers, including ourselves, have described the inhibitory effects of ouabain on lymphocyte proliferation induced by various stimuli such as mitogens [135][136][137], phorbol ester [138,139], CD3 [140], calcium ionophore [141], IL-2 [142] and to a much lesser extent IL-4 [142]. It has been reported that both CD4 and CD8 lymphocytes are equally inhibited [139].…”
Section: Effect Of Ouabain On T Lymphocyte Proliferation and Activationmentioning
confidence: 99%
“…Despite inhibiting T lymphocyte proliferation, ouabain does not affect natural killer (NK) cytotoxic activity [136] nor lymphokine activated killer (LAK) [138]. However the generation of LAK cells by IL-2 or phorbol ester is inhibited by 10 -7 M ouabain [138].…”
Section: Effect Of Ouabain On T Lymphocyte Proliferation and Activationmentioning
confidence: 99%